Virtual Reality adoption in Indonesia higher Education from lecturer’s voice - Dedi Rahman Nur (Universitas PGRI Madiun, 2020)
Indonesia's development of information and communication technology has overgrown. This can be seen by users of smartphones, a variety of Indonesian blogs, facebook or other social media and internet users. Virtual Reality is one of the information and communication technologies which started to develop in Indonesia. For this study the exploratory design approach was used to investigate the perceptions of lecturers regarding the teaching and learning adoption of VR with some indicators the benefits, ease of use, Challenges to the Adoption and skill of VR, that VR has the potential to enrich with interactive simulations and stunning visuals that immerse students in authentic learning experiences also it can push the boundaries of the traditional classroom to be engaging, creative, and responsive to the needs of the student.